Human red blood cell behavior under homogeneous extensional flow in a hyperbolic-shaped microchannel - Yaginuma, Tomoko (2013)
It is well known that certain pathological conditions result in a decrease of red blood cells (RBCs) deformability and subsequently can significantly alter the blood flow in microcirculation, which may block capillaries and cause ischemia in the tissues. Microfluidic systems able to obtain reliable quantitative measurements of RBC deformability hold the key to understand and diagnose RBC related diseases. In this work, a microfluidic system composed of a microchannel with a hyperbolic-shaped contraction followed by a sudden expansion is presented. We provide a detailed quantitative description of the degree of deformation of human RBCs under a controlled homogeneous extensional flow field. We measured the deformation index (DI) as well as the velocity of the RBCs travelling along the centerline of the channel for four different flow rates and analyze the impact of the particle Reynolds number. The results show that human RBC deformation tends to reach a plateau value in the region of constant extensional rate, the value of which depends on the extension rate. Additionally, we observe that the presence of a sudden expansion downstream of the hyperbolic contraction modifies the spatial distribution of cells and substantially increases the cell free layer (CFL downstream of the expansion plane similarly to what is seen in other expansion flows. Beyond a certain value of flow rate, there is only a weak effect of inlet flow rates on the enhancement of the downstream CFL. These in vitro experiments show the potential of using microfluidic systems with hyperbolic-shaped microchannels both for the separation of the RBCs from plasma and to assess changes in RBC deformability in physiological and pathological situations for clinical purposes. However, the selection of the geometry and the identification of the most suitable region to evaluate the changes on the RBC deformability under extensional flows are crucial if microfluidics is to be used as an in vitro clinical methodology to detect circulatory diseases.